Cobalt‐doped Cu6Sn5 lithium‐ion battery anodes with enhanced electrochemical properties. Issue 8 (29th April 2022) - Tan, Xin F.; Tao, Shiwei; Ran, Lingbing; Knibbe, Ruth; Nogita, Kazuhiro
Abstract: Sn‐based lithium‐ion battery anodes show improved capacities over commercial carbon‐based anodes. Furthermore, their higher lithiation potentials reduce the risks of Li dendrite formation. A simple Cu6 Sn5 fabrication method has been previously demonstrated, but the resultant anode shows a poor reversible capacity of 470 mAh g –1 . This study investigates the effects of Co in modifying the microstructure, crystal structure and electrochemical properties of Cu6 Sn5 to improve the electrochemical performances of the electrode. Significant enhancement in the electrochemical properties were obtained in the Co‐doped Cu6 Sn5 electrodes, where a cycling capacity as high as 830 mAh g –1 was observed during the early cycles, and a 35% increase in capacity over the pristine electrode is retained over 50 cycles. In addition, the pristine electrode does not function at a current of 0.64 mA cm –2 and above, while the Co‐doped electrode can retain a capacity of 410 mAh g –1 at a current of 1.28 mA cm –2 (2.4C). Detailed characterization of the electrodes revealed that the improved electrochemical performances are due to the refined microstructure and a higher reaction voltage during the second stage of the lithiation reaction which promotes a deeper lithiation. Abstract : This research presents a method to enhance the electrochemical performance of Cu6 Sn5 anodes via Co doping. The Co‐doped electrode shows a 35% increase in the 50th cycle capacity and improved rate capability compared to the pristine electrode. Co refines the Cu6 Sn5 grain size, providing more surface for lithiation/delithiation, and promotes a deeper lithiation by increasing the lithiation voltage.